1993
DOI: 10.1002/neu.480241203
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factors: Putative muscle‐derived trophic agents that promote motoneuron survival

Abstract: Treatment of chick embryos in ovo with IGF-I during the period of normal, developmentally regulated neuronal death (embryonic days 5-10) resulted in a dose-dependent rescue of a significant number of lumbar motoneurons from degeneration and death. IGF-II and two variants of IGF-I with reduced affinity for IGF binding proteins, des(1-3) IGF-I and long R3 IGF-I, also elicited enhanced survival of motoneurons equal to that seen in IGF-I-treated embryos. IGF-I did not enhance mitogenic activity in motoneuronal pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(97 citation statements)
references
References 71 publications
4
92
1
Order By: Relevance
“…This study demonstrates that insulin and insulin-like molecules IGF-I and IGF-II can inhibit apoptosis of E12 telencephalic cells. These results are supported by other studies illustrating that both IGF-I and IGF-II promote survival in many neuronal systems (Lindholm et al, 1996;D'Mello et al, 1993;Neff et al, 1993;Aizenman and de Vellis, 1987). The mechanism by which IGF-I mediates effects in other systems involves IGF-I receptor activation and PI3K pathways (Singleton et al, 1996a,b;Matthews and Feldman, 1996;D'Mello et al, 1997), and results presented here indicate a similar mechanism is used by immature telencephalic cells.…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrates that insulin and insulin-like molecules IGF-I and IGF-II can inhibit apoptosis of E12 telencephalic cells. These results are supported by other studies illustrating that both IGF-I and IGF-II promote survival in many neuronal systems (Lindholm et al, 1996;D'Mello et al, 1993;Neff et al, 1993;Aizenman and de Vellis, 1987). The mechanism by which IGF-I mediates effects in other systems involves IGF-I receptor activation and PI3K pathways (Singleton et al, 1996a,b;Matthews and Feldman, 1996;D'Mello et al, 1997), and results presented here indicate a similar mechanism is used by immature telencephalic cells.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous report, we showed that increased expression of IGF-I in the telencephalic wall during embryonic development and in the cerebral cortex during early postnatal development produced increases in cortical plate volume (52%) and total cell number (54%) in Tg embryos by E16, as well as increases in total cortical volume (31%) and neuron number (27%) in Tg mice by postnatal day 12 (Popken et al, 2004). However, given that IGF-I is well documented to inhibit apoptosis in vitro (Bozyczko-Coyne et al, 1993;Hughes et al, 1993;Neff et al, 1993;Mathews and Feldman, 1996;Dudek et al, 1998;Blair et al, 1999;Yamada et al, 2001) and postnatally in vivo (Baker et al, 1999;Chrysis et al, 2001), it was not clear to what extent, if any, this increased cell number resulted from an IGF-I-mediated enhancement of proliferation. Parameters that regulate neurogenesis and influence neuron output include cell cycle kinetics, progenitor cell number, and the proportion of cells exiting the cell cycle after any given division (Caviness et al, 1995;Takahashi et al, 1996Takahashi et al, , 1997Haydar et al, 2000;Chenn and Walsh, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…The role of IGF-1 in motor neurone survival has been examined during embryonic or postnatal life (Neff et al, 1993) as well as in spinal cord pathology (Rind & von Bartheld, 2002). For example, in young rodents IGF-1 expression is up-regulated in Schwann cells and astrocytes following spinal cord and peripheral nerve injury, while IGF-binding protein 6 is strongly upregulated in injured motorneurones (Hammarberg et al, 1998 Interestingly, in regions of muscle enriched with neuromuscular junctions, IGF-II exhibited prominent up-regulation in satellite and possibly glial cells during recovery from sciatic nerve crush (Pu et al, 1999) while IGF-I showed less significant changes.…”
Section: Effects Of Igf-1 On Neuronesmentioning
confidence: 99%